Nurses’ Knowledge of the Early Warning Scoring (EWS) System Based on Demographic Characteristics at RSU Imelda Pekerja Indonesia. - Arta Marisi Dame Panggabean; Satriani Hartalina Gultom; Ronal Mental Lius Hulu (Benih : Journal of Midwifery, 2026)
Background: Nurses' knowledge of EWS is one of the factors influencing patient detection in hospitals. Objective: This study aims to determine the description of nurses' knowledge of EWS based on characteristics at Imelda Regional Hospital, Indonesian Workers in 2024. Method: This study used descriptive research. The population was 137 people with a sample of 58 people. Sampling in this study was carried out using accidental sampling technique. Results: The study showed the results of the characteristics of respondents according to age that the most were in the 25-29 year age group with 23 respondents (39.7%). Based on gender, the majority of nurses were female with 42 respondents (72.4%). The majority of respondents were at the D3 Nursing education level with 30 respondents (51.7%). The majority of respondents were in the work period >3 years (long) with 38 respondents (65.5%). Meanwhile, the majority of respondents who participated in training were 55 respondents (94.8%). The frequency distribution of nurses' knowledge about EWS had sufficient knowledge with 46 respondents (79.3%). The most knowledgeable based on age 25-29 years as many as 17 respondents (73.3%), the most knowledgeable based on gender as many as 33 respondents (78.6%), the most knowledgeable based on D3 Nursing education as many as 26 respondents (86.7%), the most knowledgeable based on length of service category (>3 years) as many as 32 respondents (84.2%), the most knowledgeable based on training attended as many as 45 respondents (81.8%). Conclusion: Nurses' knowledge affects their ability to identify patients with worsening patient conditions. Suggestion: It is recommended that hospitals provide EWS training for those who have never attended training and those who have received training for new nurses, and for experienced nurses to be refreshed so that nurses' knowledge can continue to be improved.